Electrochemical characterization of 1-ethyl-3-methylimidazolium thiocyanate and measurement of triiodide diffusion coefficients in blends of two ionic liquids - Zistler, Markus; Schreiner, Christian; Wachter, Philipp; Wasserscheid, Peter; Gerhard, Dirk; Gores, Heiner J. (International Journal of Electrochemical Science, 2008)
According to literature, binary mixtures of ionic liquids (ILs) such as 1-methyl-3-propylimidazolium iodide (MPII) as an iodide source and another IL of low viscosity such as 1-ethyl-3- methylimidazolium thiocyanate (EMISCN) may be used to increase the diffusion coefficients of redox-active species (I-/I3 -). As dye-sensitized solar cells (DSCs) are diffusion limited a better performance may result with blends when compared to cells based on MPII alone. In order to learn more about EMISCN and its blends with MPII, we electrochemically characterized this IL and measured diffusion coefficients of triiodide in binary mixtures containing EMISCN by polarization and impedance studies at thin layer cells with a distance between Pt-electrodes of about 30 to 40 μm. The electrochemical windows of the used ILs were measured by cyclic voltammetry (CV) and compared to those of other ILs, recently investigated by us. © 2008 by ESG.
Keywords: Cyclic voltammetry; Diffusion measurement; Dye-sensitized solar cell; Electrochemical stability; Ionic liquids